Stakeholder involvement in care transition planning for older adults and the factors guiding their decision-making: a scoping review - Whitney Berta; Kerry Kuluski; Kristina Marie Kokorelias; Susan Law; Sarah Carbone (BMJ Open)
Objective To synthesise the existing literature on care transition planning from the perspectives of older adults, caregivers and health professionals and to identify the factors that may influence these stakeholders’ transition decision-making processes.Design A scoping review guided by Arksey and O’Malley’s six-step framework. A comprehensive search strategy was conducted on 7 January 2021 to identify articles in five databases (MEDLINE, Embase, CINAHL Plus, PsycINFO and AgeLine). Records were included when they described care transition planning in an institutional setting from the perspectives of the care triad (older adults, caregivers and health professionals). No date or study design restrictions were imposed.Setting This review explored care transitions involving older adults from an institutional care setting to any other institutional or non-institutional care setting. Institutional care settings include communal facilities where individuals dwell for short or extended periods of time and have access to healthcare services.Participants Older adults (aged 65 or older), caregivers and health professionals.Results 39 records were included. Stakeholder involvement in transition planning varied across the studies. Transition decisions were largely made by health professionals, with limited or unclear involvement from older adults and caregivers. Seven factors appeared to guide transition planning across the stakeholder groups: (a) institutional priorities and requirements; (b) resources; (c) knowledge; (d) risk; (e) group structure and dynamic; (f) health and support needs; and (g) personality preferences and beliefs. Factors were described at microlevels, mesolevels and macrolevels.Conclusions This review explored stakeholder involvement in transition planning and identified seven factors that appear to influence transition decision-making. These factors may be useful in advancing the delivery of person and family-centred care by determining how individual-level, group-level and system-level values guide decision-making. Further research is needed to understand how various stakeholder groups balance these factors during transition planning in different health contexts.